Can Rewards Improve Students' Literacy Skills? - Putri, Idra (Jurnal Pendidikan Profesi Guru, 2024)
This research aims to see to what extent the effectiveness of giving rewards can improve the literacy skills of students at Madrasah Tsanawiyah Negeri 1 Padang City. This research was conducted using a mixed quantitative method. The research subjects were MTsN 1 Padang City students. This research consists of 2 cycles with the actions taken moving from the initial conditions. Each cycle consists of four steps, namely planning, implementation, observation, and reflection. Based on data on student participation in the Biography of Buya Hamka writing competition on Fairy Reward, Literacy, students remember Islamic holidays at MTsN 1 Padang City in the July-August 2023 period, an average of 81.36%. Meanwhile, for the August-September 2023 period it was 96.61%. Thus there was a significant increase of 15.25%. The average student participation in the competition exceeded the success target after being given a reward, so this method is suitable for increasing student participation in improving literacy skills in madrasas. Furthermore, based on the analysis of this research data, it can be concluded that giving rewards is effective in improving students' literacy skills in teaching and learning activities at MTsN 1 Padang City.